An Exploration the impacts of Industrialisation and Environment in Nagpur, Maharashtra (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Industrialization is a government plan to diversify and empower a region's economy based on its resources. The resource base of a region must be studied & developed before its industrial potential may be used. Groundwater levels and groundwater extraction are investigated to see if they are affected by climate variability. The primary goal of the industrial & impact of Environment report was to document the state of the environment in Nagpur. This will provide a rational framework for planners, policymakers, and citizens to make decisions that are conducive to environmental conservation. The analysis begins by mapping the industrial landscape of Nagpur, highlighting key sectors and their contributions to economic growth. Special attention is paid to the types of industries, their scale, and the associated resource consumption and waste generation. Subsequently, the study delves into the environmental repercussions of this industrial surge, exploring issues such as air and water pollution, deforestation, and biodiversity loss. the study investigates the environmental policies and regulations in place, assessing their effectiveness in mitigating the adverse impacts of industrialization.